Transitioning from traditional to problem-based learning in management education: the case of a frontline manager skills development programme. Issue 3 (4th May 2017) - Delaney, Yvonne; Pattinson, Bob; McCarthy, John; Beecham, Sarah
Abstract : Education providers experiment with different pedagogical strategies that depart from traditional modes of delivery. Problem-based learning (PBL), which enhances and leverages practitioners' competencies and skill-sets, is one such strategy. Transitioning to PBL can prove challenging for course design teams. This paper provides evidence-based insights into this transition by detailing how a management development programme for 10 frontline managers transitioned from traditional to pilot PBL delivery. Drawing on the six stages identified in the transition, and empirical data on the student experience, five conclusions on managing the transition to PBL were identified: (1) critical involvement and input of stakeholders external to the course design team; (2) need to adapt PBL for institutional, discipline and cohort fit; (3) importance of preparing the student cohort to cope with the inherent tensions of PBL; (4) managing their potential demands for additional control; (5) clarification of opportunity and resource costs that arise from implementing PBL.